Lasting Impact of Clostridium difficile Infection in Inflammatory Bowel Disease: A Propensity Score Matched Analysis. Issue 12 (December 2017) - Anderson, Alyce; Click, Benjamin; Ramos-Rivers, Claudia; Cheng, Debbie; Babichenko, Dmitriy; Koutroubakis, Ioannis E.; Hashash, Jana G.; Schwartz, Marc; Swoger, Jason; Barrie, Arthur M.; Dunn, Michael A.; Regueiro, Miguel; et al.
Abstract : Background: Patients with inflammatory bowel disease are at an increased risk of Clostridium difficile infection (CDI), but the impact of CDI on disease severity is unclear. The aim of this study was to determine the effect of CDI on long-term disease outcome in a matched cohort of patients with inflammatory bowel disease. Methods: Patients who tested positive for infection formed the CDI-positive group. We generated a 1:2 propensity matched case to control cohort based on risk factors for CDI in the year before infection. Health care utilization data (emergency department use, hospitalizations, and telephone encounters), medications, laboratories, disease activity, and quality-of-life metrics were compared by CDI status. Results: A total of 198 patients (66 CDI and 132 matched controls) were included (56.6% women; 60.1% Crohn's disease, and 39.9% ulcerative colitis). In the year of infection, having CDI was significantly associated with more steroid and antibiotic exposure, elevated C-reactive protein or erythrocyte sedimentation rate, low vitamin D, increased disease activity, worse quality of life, and increased health care utilization (all P < 0.01). During the next year after infection, patients with CDI continued to have increased exposure to CDI-targeted antibiotics ( P < 0.001) and other antibiotics ( P = 0.02). They also continued to have more clinic visits ( P = 0.02), telephone encounters ( P = 0.001), and increased health care financial charges ( P = 0.001). Conclusions: CDI in inflammatory bowel disease is significantly associated with markers of disease severity, increased health care utilization and poor quality of life during the year of infection, and a 5-fold increase in health care charges in the year after infection (see Video Abstract, Supplemental Digital Content, http://links.lww.com/IBD/B658 ). Abstract : Article first published online 27 October 2017.Supplemental Digital Content is Available in the Text.